Implementasi Gadai Emas di Pegadaian Syariah Munggur, Yogyakarta Berdasarkan Fatwa Nomor 25/DSN-MUI/III/2002 dan Fatwa Nomor 26/DSN-MUI/III/2002 - Savira Mirza Arinda (CV Rewang Rencang, 2023)
Pawn or Rahn is possession of the borrower's property by the lender as collateral. The results of this study indicate that the implementation of gold pawning at the Munggur Sharia Pawnshop in Yogyakarta in its implementation there are things that are not appropriate, such as maintenance costs (ijarah) and administration costs that are not in accordance with the fatwa Number 25/DSN-MUI/III/2002 concerning Rahn, will but in accordance with fatwa No. 26/DSN-MUI/III/2002 concerning Gold Rahn. The implementation of gold pawning at the Munggur Syariah Pawnshop in Yogyakarta whole has been carried out properly in accordance with the two Fatwas.